急性期脳血管障害患者における歩行予後因子の検討 - 樋口 謙次; 安保 雅博 (理学療法学, 2008)
Purpose: The purpose of this study was to investigate the usefulness of the sitting ability at 10 days post-stroke as a factor of prognosis for walking ability within 1 month post-stroke. Methods: The subjects were 79 stroke patients suffering a first stroke. First, we divided the patients into two groups, those who could walk (independence and observation) and those who could not (partial or total assistance) on day 20 and day 30 post-stroke, and performed univariate analysis (χ^2 test and t-test) with age, consciousness disorder, higher cortical function disorder, paralysis of each of the lower limbs, and sitting ability as the variables. Then, with the object variable as ability to walk on day 20 and day 30 post-stroke, and explanatory variables as age, consciousness disorder, higher cortical function disorder, paralysis of each of the lower limbs and sitting ability, we performed multivariate analysis (logistic regression). Result: In the univariate analysis significant differences were found for consciousness disorder, higher cortical function disorder, paralysis of each of the lower limbs, and sitting ability, between ability to walk and lack of ability to walk (p<0.05). However, in multivariate analysis, only two factors, sitting ability and paralysis of each of the lower limbs, were found to be significant (p<0.05). Conclusions: Sitting ability at 10 days post-stroke may be useful as a walking prognosis factor. 【目的】本研究の目的は,脳血管障害患者の発症10日目での坐位保持能力が発症1ヶ月以内の歩行予後因子として有用であるかを検討することである。【方法】対象は初発の脳血管障害患者79例である。分析I:発症20日目及び30日目の歩行能力の可能(自立,監視),不可能(要介助,全介助)を2群に分類し,年齢,意識障害,高次脳機能障害,下肢運動麻痺,坐位保持能力について単変量解析(χ^2検定及びt-検定)をした。分析II:20日目及び30日目の歩行能力の可否を日的変数とし,坐位保持能力,年齢,意識障害,高次脳機能障害,下肢運動麻痺を説明変数として多変量解析(ロジスティック回帰分析)をした。【結果】単変量解析では,意識障害,高次脳機能障害,下肢運動麻痺,坐位保持能力において有意差が認められた(p<0.05)。しかし,多変量解析では坐位保持能力と下肢運動麻痺の2因子のみが有意に抽出された(p<0.05)。【結論】発症1ヶ月以内での歩行予後因子として,10日目の坐位保持能力は有用であることが示唆された。